Abstract 16 New Advanced Therapy Medicinal Products (ATMPs) in Medical Trials: A FamiCord Group Development Pipeline Update. (6th September 2022) - Gerth, André; Heike Opitz, Constanze; Baran, Tomasz; Oldak, Tomasz
Abstract: Introduction: Seventeen products in five countries are used in medical experiments and clinical trials. FamiCord Group, the leading stem cell bank in Europe and number 3 worldwide, is a listed biotech group consisting of the European biotech companies Vita 34 (Germany), P.B.K.M. (Poland), Crioestaminal (Portugal), Smart Cells (UK), and more than 30 other subsidiaries. FamiCord Group was founded in 2002 and is located in more than 35 countries in Europe and the Middle East. The Group is engaged in the storage of biological material and the manufacture, development, and approval of cell therapeutics for clinical use. More than 850, 000 cryopreserved umbilical cord blood and tissue units and more than 4, 200 patients treated with stem cells in clinical trials, experimental therapies, and standard therapies demonstrate the extraordinary expertise in stem cell banking and clinical application. Objective: An overview of the Cell Therapy Pipeline with cell products from the FamiCord Group is shown in Table 1. ATMPs have been developed and manufactured in 3 synergistic R&D centers in Poland, Portugal, and Germany. Twenty preclinical and clinical trials are being conducted as part of in-house and consortia projects. Methods: Selected new developments are presented in detail: BIOOPA for treatment of epidermolysis bullosa and CartiCure for treatment of cartilage damage in knee joint. Results: The BIOOPA dressing for the treatment of epidermolysis bullosa is safe and effective, as no infections or necrosis were observed at the graft implant site during the follow-up period. These patients also reported reduced pain and improved quality of life. When used in orthopedics (CartiCure for cartilage damage), cord tissue-derived MSCs have been shown to be safe and fully integrated into the patient's cartilage, resulting in significant improvement in pain scores and quality of life. Discussion: The trials presented demonstrate that allogeneic cell therapeutics are the future of regenerative medicine. Use of allogenic technology is the only way to overcome the limitations of the autologous approach: manufacturing process extensively scalable, drug available "off the shelf", applicable in all medical facilities, and economical manufacturing process due to unlimited scalability. Large pharmaceutical companies are investing significantly in this space.